Jerusalem artichoke residue-based hard carbon material and preparation method and application thereof in sodium ion battery

Through the preparation of the Jerusalem artichoke slag-based hard carbon material, the problems of existing hard carbon materials in sodium ion batteries are solved, and high-efficiency and low-cost negative electrode materials of sodium ion batteries are achieved.

CN119660716AInactive Publication Date: 2025-03-21UNIV OF JINAN
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510156844.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-13
Publication Date
2025-03-21
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing hard carbon materials face problems in sodium ion batteries, resulting in low initial Coulomb efficiency and insufficient energy density.

Method used

By using Jerusalem artichoke slag as the precursor material, through acid-base treatment and hot-pressing carbonization, hard carbon materials with a specific surface area of ​​less than 5.0 m² g⁻¹ and a tap density of up to 0.8 g cm⁻³ were prepared.

Benefits of technology

The material has a high reversible capacity of 350 mAh g⁻¹ at 20 mA g⁻², an initial Coulombic efficiency of 92.1%, and exhibits good rate performance. It is suitable for the negative electrode material of sodium ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119660716A_ABST
    Figure CN119660716A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of sodium ion batteries, and particularly relates to a jerusalem artichoke residue-based hard carbon material, a preparation method thereof and application of the jerusalem artichoke residue-based hard carbon material in a sodium ion battery. The preparation method of the hard carbon material comprises the following steps: performing acid-base chemical heat treatment on jerusalem artichoke residues to obtain a precursor material with adjustable components, and carbonizing to obtain the electrode material. The method realizes secondary utilization of wastes, and has the characteristics of economy, environmental protection and the like. According to the invention, the jerusalem artichoke slag is used as a precursor, the hard carbon material at the optimal carbonization temperature is prepared by a method of heating and soaking the jerusalem artichoke slag together with acid and alkali, the specific surface area is lower than 5.0 m < 2 > g <-1 >, the tap density is as high as 0.8 g cm <-3 >, and the storage capacity of sodium and the cycling stability of the material are effectively improved. The jerusalem artichoke residue-based hard carbon material can be used for preparing sodium ion batteries and has important application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of sodium ion batteries, and in particular relates to a Jerusalem artichoke residue-based hard carbon material, a preparation method thereof, and application of the material in sodium ion batteries. Background Art

[0002] The information disclosed in this background section is intended to enhance understanding of the overall background of the invention and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.

[0003] Among various energy storage technologies, lithium-ion batteries stand out from many electrochemical energy storage devices due to their advantages such as high energy density, fast conversion efficiency, and long cycle life. They are widely used in large-scale energy storage, electric vehicles, portable electronic devices, etc. However, since lithium resources are limited and unevenly distributed, the use of organic electrolytes requires further improvement in safety, which is not conducive to their long-term development. Due to its low cost and abundant sodium resources, sodium-ion batteries are considered to be one of the most promising batteries in large-scale energy storage and low-speed electric vehicles. Although many positive electrode materials have been developed, the lack of high-performance negative electrode materials has seriously restricted the improvement of the energy density of sodium-ion batteries. Therefore, innovating economically feasible and high-performance negative electrode materials is crucial to promote the development of sodium-ion batteries.

[0004] Among the various existing negative electrode materials, hard carbon has a high specific capacity (~300 mAhg -1 ), low working potential (~0.1V) and long cycle life, and is considered to be the most promising negative electrode material. The initial coulombic efficiency is one of the main performance indicators of hard carbon materials, but due to the structural characteristics of hard carbon materials, there is a general problem of low initial coulombic efficiency. The main reasons include surface defects and the formation of SEI film. The specific surface area is a key factor affecting its initial coulombic efficiency and cycle stability. Although a higher specific surface area can increase the specific capacity of the material, it will also lead to more sodium ions being used to form the SEI film, thereby reducing the initial coulombic efficiency. At present, the specific surface area of ​​commercialized hard carbon is usually around 5m² g -1In order to reduce the specific surface area, the surface chemical properties of the material can be improved by optimizing the carbonization process, introducing heteroatoms, surface coating and other methods. For example, asphalt carbon coating and gas-phase carbon source pyrolysis deposition can form a relatively dense structure on the hard carbon surface, thereby improving the initial Coulomb efficiency of the material. At the same time, the tap density of hard carbon negative electrode materials is one of the key factors affecting the volume energy density of the battery. The tap density is closely related to the structure and physical strength of the material, and is also related to the particle size distribution and porosity of the material powder. Hard carbon materials usually have a rich pore structure, which helps to improve the specific capacity, but also leads to a low tap density, which limits its performance in practical applications. The tap density of currently commercialized hard carbon is generally between 0.55-0.8g cm -3 In order to improve the tap density of hard carbon, researchers have tried to improve the tap density of materials by improving the pore structure distribution, increasing the residual carbon rate of carbon source, and optimizing the particle size distribution of materials. Summary of the invention

[0005] In view of the shortcomings of the prior art, the first object of the present invention is to provide a method for preparing a Jerusalem artichoke residue-based hard carbon material, which has the advantages of simple operation and easy control. In addition, the raw materials used in the method are low-priced and green and environmentally friendly, and are easy to prepare low-cost and high-performance hard carbon on a large scale. In view of the problems of tap density and specific surface area faced by existing hard carbon materials, the method for preparing a hard carbon material from Jerusalem artichoke residue provided by the present invention is low-cost, and the specific surface area of ​​the hard carbon material prepared by the method is less than 5.0 m 2 g -1 , with a tap density of up to 0.8 g cm -3 The prepared electrode material has good electrochemical performance at 20 mA g -2 350 mAh g -1 The high reversible capacity, initial coulombic efficiency of 92.1%, and good rate performance (2 A g -1 Capacity: 203 mAh g -1 ).

[0006] The second object of the present invention is to provide a raw material and a preparation method of a biomass hard carbon material with high tap density and low specific surface area.

[0007] The third object of the present invention is to provide applications of the above electrode material.

[0008] To achieve the above object, the present invention adopts the following technical solution: A method for preparing a Jerusalem artichoke residue-based hard carbon electrode material, the preparation method comprising the following steps: (1) Soak the precursor material in deionized water, wash away the surface impurities and dust with an ultrasonic cleaner, filter and dry the water in an oven; (2) The dried precursor material is crushed by an electric pulverizer to obtain a homogeneous powder, which is then immersed in an acidic solution for heat treatment to directionally remove lignin from the precursor material. The solution is filtered and washed with deionized water to a pH of 7, and then placed in a freeze drying oven to obtain a precursor material after some lignin has been removed. (3) The precursor material after removing part of the lignin obtained in step (2) is immersed in an alkaline solution for heat treatment to further directionally remove the hemicellulose in the material, the solution is filtered and washed with deionized water to pH = 7, and placed in a freeze drying box to obtain the precursor material after removing part of the hemicellulose; (4) placing the precursor material after removing part of the hemicellulose in step (3) under a hot press for heating and compression, so that the cellulose in the material is densely packed to obtain a dense precursor material; (5) placing the dense precursor material obtained in step (4) in an inert atmosphere, introducing an inert gas as a protective gas into a tubular furnace for carbonization, and after the carbonization is completed, the furnace body naturally cools down to room temperature to obtain a carbonized material; (6) Grind and crush the carbonized material obtained in step (5) and transfer it to an acidic solution, stir and wash it, then filter it with deionized water until it is neutral to remove impurities, and then dry it and sieve it to obtain the Jerusalem artichoke residue-based hard carbon material for sodium ion battery electrode material.

[0009] Furthermore, in step (1), the precursor material is Jerusalem artichoke residue.

[0010] Furthermore, in step (2), the acidic solution is an acetic acid solution of sodium hypochlorite, an aqueous sulfuric acid solution or an aqueous hydrofluoric acid (HF) solution.

[0011] Furthermore, the acetic acid solution of sodium hypochlorite is a yellow-green solution prepared by mixing sodium hypochlorite, acetic acid and deionized water in a mass volume ratio of (2-8) g: (0.5-16) mL: (30-1000) mL; the mass fraction of the aqueous sulfuric acid solution is 30-70 wt%; and the mass fraction of the aqueous hydrofluoric acid solution is 5-30 wt%.

[0012] Furthermore, in step (2), the heat treatment soaking time is 2-12 h, and the heating temperature is 60-100°C.

[0013] Furthermore, in step (3), the alkaline solution is a sodium hydroxide aqueous solution with a concentration of 2-10 wt% or a potassium hydroxide aqueous solution with a concentration of 2-10 wt%.

[0014] Furthermore, in step (3), the heat treatment soaking time is 2-12 h, and heating is performed during soaking at a heating temperature of 60-100°C.

[0015] Furthermore, in step (5), the carbonization temperature is 800-1600°C, the heating rate is 1-10°C / min, and the carbonization temperature is maintained for 0.1-6 h after reaching the above carbonization temperature.

[0016] Furthermore, in step (5), the inert atmosphere is nitrogen or a hydrogen-argon mixture (1%:99%).

[0017] Furthermore, in step (6), the acidic solution is a solution of hydrochloric acid and deionized water with a concentration of (2-8 wt%).

[0018] The Jerusalem artichoke residue-based hard carbon electrode material prepared by the above method has a rich closed-pore content and a pore size suitable for the embedding and de-embedding of sodium ions.

[0019] Application of the above electrode material: the electrode material can be used in the field of sodium ion batteries.

[0020] Beneficial effects: 1. The present invention successfully synthesizes a series of derivative hard carbon materials by regulating temperature and precursor components. The Jerusalem artichoke residue after acid and alkali treatment contains a large amount of crystalline cellulose, which can be converted into long graphene sheets, which serve as the wall of the closed pores, surrounding and shrinking the active sites to form a closed pore structure. The presence of amorphous components (hemicellulose and lignin) not only contributes to the nano-sizing of the carbon layer, but also prevents the excessive graphitization of the carbon layer during high-temperature carbonization. With the increase of carbonization temperature, the length of the graphite-like carbon layer increases, which is conducive to the formation of a closed pore structure, thereby having superior capacity. The present invention provides a strategy for the preparation of low-cost hard carbon negative electrodes for sodium ion batteries with high reversible capacity, low specific surface area and high tap density in the future; the preparation method provided by the present invention has the advantages of simple operation, easy control, low price of waste raw materials used and green environmental protection, and is easy to prepare low-cost and high-performance hard carbon on a large scale.

[0021] 2. The electrode material prepared by the present invention has a high tap density, contains a large number of closed pores inside, and has a low specific surface area, which is conducive to reducing unnecessary side reactions. Therefore, it has a high reversible specific capacity and initial coulombic efficiency, and good rate performance, and can be used in the field of sodium ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention, and the exemplary embodiments of the present invention and their description are used to explain the present invention, and do not constitute an improper limitation of the present invention.

[0023] Figure 1The X-ray diffraction pattern of the electrode material prepared in Example 1; Figure 2 A scanning electron microscope image of the electrode material prepared in Example 1; Figure 3 A transmission electron microscope image of the electrode material prepared in Example 1; Figure 4 The rate performance of the sodium ion batteries prepared in Examples 1-3 and Comparative Example 1 at different current densities; Figure 5 The figure is a statistical graph of the charge and discharge specific capacity of the sodium ion batteries prepared in Examples 1-3 and Comparative Example 1 at a current density of 20 mA / g. DETAILED DESCRIPTION

[0024] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0025] Unless otherwise defined, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. The reagents or raw materials used in the present invention can be purchased through conventional channels. If not otherwise specified, the reagents or raw materials used in the present invention are used in a conventional manner in the art or in accordance with the product instructions. In addition, any method and material similar to or equivalent to the described content can be applied to the method of the present invention. The preferred implementation methods and materials described in the present invention are for demonstration purposes only. The present invention is further described according to the accompanying drawings and specific embodiments of the specification.

[0026] Example 1 (1) Soak the Jerusalem artichoke residue in deionized water, wash away the impurities and dust on the surface with an ultrasonic cleaner, filter and dry the residue in an oven; (2) The dried precursor material was crushed by an electric pulverizer to obtain a homogeneous powder, which was then immersed in a yellow-green solution of 4 g sodium hypochlorite and 8 mL acetic acid dissolved in 600 mL deionized water for heat treatment at 80 °C for 8 h. The filtrate was filtered out and washed with deionized water to pH = 7. The precursor material was placed in a freeze drying oven for drying to obtain a precursor material after removing part of the lignin. (3) The precursor material after removing part of the lignin obtained in step (2) is immersed in a sodium hydroxide solution with a concentration of 5 wt%, and is also subjected to a heat treatment at 80°C for 8 h to further directionally remove the hemicellulose in the material. The solution is filtered and washed with deionized water to a pH of 7, and then placed in a freeze drying oven for drying to obtain a precursor material after removing the hemicellulose; (4) placing the precursor material after removing part of the hemicellulose in step (3) under a hot press for heating and compression to allow the cellulose to be densely packed to obtain a dense material; (5) placing the dense material obtained in step (4) in an inert nitrogen atmosphere, and carbonizing it at 1400°C in a tube furnace at a heating rate of 2°C / min and a holding time of 2 h to obtain a carbonized solid; (6) Grind and crush the carbonized material obtained in step (5) and transfer it to an acidic solution, stir and wash it, then filter it with deionized water until it is neutral, and then dry it and sieve it to obtain the Jerusalem artichoke residue-based hard carbon material for sodium ion battery electrode material.

[0027] Figure 1 The X-ray diffraction pattern of the electrode material prepared in Example 1; Figure 2 A scanning electron microscope image of the front electrode material prepared in Example 1; Figure 3 This is a transmission electron microscope image of the electrode material prepared in Example 1.

[0028] Example 2 (1) Soak the Jerusalem artichoke residue in deionized water, wash away the impurities and dust on the surface with an ultrasonic cleaner, filter and dry the residue in an oven; (2) The dried precursor material was crushed by an electric pulverizer to obtain a homogeneous powder, which was then immersed in a yellow-green solution of 2 g sodium hypochlorite and 4 mL acetic acid dissolved in 300 mL deionized water for heat treatment at 60°C for 12 h. The filtrate was filtered out and washed with deionized water to pH = 7, and placed in a freeze drying oven to obtain a precursor material after removing part of the lignin. (3) The precursor material after removing part of the lignin obtained in step (2) is immersed in a sodium hydroxide solution with a concentration of 2 wt% and subjected to a heat treatment at 100°C for 2 h to further directionally remove the hemicellulose in the material. The solution is filtered and washed with deionized water to a pH of 7, and placed in a freeze drying oven to obtain the precursor material after removing the hemicellulose; (4) placing the precursor material after the hemicellulose is removed in step (3) under a hot press for heating and compression to allow the cellulose to be densely packed to obtain a dense material; (5) placing the dense material obtained in step (4) in a nitrogen atmosphere, and carbonizing it at 800°C in a tube furnace at a heating rate of 1°C / min and a holding time of 6 h to obtain a carbonized solid; (6) Grind and crush the carbonized material obtained in step (5) and transfer it to an acidic solution, stir and wash it, then filter it with deionized water until it is neutral, and then dry it and sieve it to obtain the Jerusalem artichoke residue-based hard carbon material for sodium ion battery electrode material.

[0029] Example 3 (1) Soak the Jerusalem artichoke residue in deionized water, wash away the impurities and dust on the surface with an ultrasonic cleaner, filter and dry the residue in an oven; (2) The dried precursor material was crushed by an electric pulverizer to obtain a homogeneous powder, which was then immersed in a yellow-green solution of 8 g sodium hypochlorite and 16 mL acetic acid dissolved in 1000 mL deionized water for heat treatment at 100 ° C for 2 h. The filtrate was filtered out and washed with deionized water to pH = 7. The precursor material was placed in a freeze drying oven to obtain a precursor material after removing part of the lignin. (3) The precursor material after removing part of the lignin obtained in step (2) is immersed in a sodium hydroxide solution with a concentration of 5 wt% and subjected to a heat treatment at 100°C for 2 h to further directionally remove the hemicellulose in the material. The solution is filtered and washed with deionized water to a pH of 7, and then placed in a freeze drying oven for drying to obtain the precursor material after removing the hemicellulose. (4) placing the precursor material after the hemicellulose is removed in step (3) under a hot press for heating and compression to allow the cellulose to be densely packed to obtain a dense material; (5) placing the dense material obtained in step (4) in a hydrogen-argon mixed gas (1%:99%) atmosphere, and carbonizing it at 1600°C in a tube furnace at a heating rate of 10°C / min and a holding time of 0.1 h to obtain a carbonized solid; (6) Grind and crush the carbonized material obtained in step (5) and transfer it to an acidic solution, stir and wash it, then filter it with deionized water until it is neutral, and then dry it and sieve it to obtain the Jerusalem artichoke residue-based hard carbon material for sodium ion battery electrode material.

[0030] Example 4 (1) Soak the Jerusalem artichoke residue in deionized water, wash away the impurities and dust on the surface with an ultrasonic cleaner, filter and dry the residue in an oven; (2) The dried precursor material was crushed by an electric pulverizer to obtain a homogeneous powder, which was then immersed in 500 mL of a 30 wt% hydrofluoric acid aqueous solution for heat treatment at 80°C for 8 h. The filtrate was filtered out and washed with deionized water until the pH value was 7. The precursor material was placed in a freeze drying oven for drying to obtain a precursor material after removing part of the lignin. (3) The precursor material after removing part of the lignin obtained in step (2) is immersed in a potassium hydroxide solution with a concentration of 5 wt%, and is also subjected to a heat treatment at 80°C for 8 h to further directionally remove the hemicellulose in the material. The solution is filtered and washed with deionized water to a pH of 7, and then placed in a freeze drying oven for drying to obtain a precursor material after removing the hemicellulose; (4) placing the precursor material after the hemicellulose is removed in step (3) under a hot press for heating and compression to allow the cellulose to be densely packed to obtain a dense material; (5) placing the dense material obtained in step (4) in an inert nitrogen atmosphere, and carbonizing it at 1400°C in a tube furnace at a heating rate of 2°C / min and a holding time of 2 h to obtain a carbonized solid; (6) Grind and crush the carbonized material obtained in step (5) and transfer it to an acidic solution, stir and wash it, then filter it with deionized water until it is neutral, and then dry it and sieve it to obtain the Jerusalem artichoke residue-based hard carbon material for sodium ion battery electrode material.

[0031] Example 5 (1) Soak the Jerusalem artichoke residue in deionized water, wash away the impurities and dust on the surface with an ultrasonic cleaner, filter and dry the residue in an oven; (2) The dried precursor material was crushed by an electric pulverizer to obtain a homogeneous powder, which was then immersed in 500 mL of a 70 wt% sulfuric acid aqueous solution for heat treatment at 80°C for 8 h. The filtrate was filtered out and washed with deionized water until the pH value was 7. The precursor material was placed in a freeze drying oven for drying to obtain a precursor material after removing part of the lignin. (3) The precursor material after removing part of the lignin obtained in step (2) is immersed in a sodium hydroxide solution with a concentration of 5 wt%, and is also subjected to a heat treatment at 80° C. for 8 h to further directionally remove the hemicellulose in the material. The solution is filtered and washed with deionized water to a pH of 7, and then placed in a freeze drying oven for drying to obtain a precursor material after removing the hemicellulose; (4) placing the precursor material after the hemicellulose is removed in step (3) under a hot press for heating and compression to allow the cellulose to be densely packed to obtain a dense material; (5) placing the dense material obtained in step (4) in an inert nitrogen atmosphere, and carbonizing it at 1400°C in a tube furnace at a heating rate of 2°C / min and a holding time of 2 h to obtain a carbonized solid; (6) Grind and crush the carbonized material obtained in step (5) and transfer it to an acidic solution, stir and wash it, then filter it with deionized water until it is neutral, and then dry it and sieve it to obtain the Jerusalem artichoke residue-based hard carbon material for sodium ion battery electrode material.

[0032] Example 6 (1) Soak the Jerusalem artichoke residue in deionized water, wash away the impurities and dust on the surface with an ultrasonic cleaner, filter and dry the residue in an oven; (2) The dried precursor material was crushed by an electric pulverizer to obtain a homogeneous powder, which was then immersed in 500 mL of a 30 wt% sulfuric acid aqueous solution for heat treatment at 80°C for 8 h. The filtrate was filtered out and washed with deionized water until the pH value was 7. The precursor material was placed in a freeze drying oven for drying to obtain a precursor material after removing part of the lignin. (3) The precursor material after removing part of the lignin obtained in step (2) is immersed in an alkaline solution of potassium hydroxide with a concentration of 2 wt%, and is also subjected to a heat treatment at 80°C for 8 h to further directionally remove the hemicellulose in the material. The solution is filtered and washed with deionized water to a pH of 7, and then placed in a freeze drying oven for drying to obtain a precursor material after removing the hemicellulose; (4) placing the precursor material after the hemicellulose is removed in step (3) under a hot press for heating and compression to allow the cellulose to be densely packed to obtain a dense material; (5) placing the dense material obtained in step (4) in an inert nitrogen atmosphere, and carbonizing it at 1400°C in a tube furnace at a heating rate of 2°C / min and a holding time of 2 h to obtain a carbonized solid; (6) Grind and crush the carbonized material obtained in step (5) and transfer it to an acidic solution, stir and wash it, then filter it with deionized water until it is neutral, and then dry it and sieve it to obtain the Jerusalem artichoke residue-based hard carbon material for sodium ion battery electrode material.

[0033] Example 7 (1) Soak the Jerusalem artichoke residue in deionized water, wash away the impurities and dust on the surface with an ultrasonic cleaner, filter and dry the residue in an oven; (2) The dried precursor material was crushed by an electric pulverizer to obtain a homogeneous powder, which was then immersed in 500 mL of a 30 wt% sulfuric acid aqueous solution for heat treatment at 80°C for 8 h. The filtrate was filtered out and washed with deionized water until the pH value was 7. The precursor material was placed in a freeze drying oven for drying to obtain a precursor material after removing part of the lignin. (3) The precursor material after removing part of the lignin obtained in step (2) is immersed in an alkaline solution of potassium hydroxide with a concentration of 10 wt%, and is also subjected to a heat treatment at 80° C. for 8 h to further directionally remove the hemicellulose in the material. The solution is filtered and washed with deionized water to a pH of 7, and then placed in a freeze drying oven for drying to obtain a precursor material after removing the hemicellulose; (4) placing the precursor material after the hemicellulose is removed in step (3) under a hot press for heating and compression to allow the cellulose to be densely packed to obtain a dense material; (5) placing the dense material obtained in step (4) in a nitrogen inert atmosphere, and carbonizing it at 1400°C in a tube furnace at a heating rate of 2°C / min and a holding time of 2 h to obtain a carbonized solid; (6) Grind and crush the carbonized material obtained in step (5) and transfer it to an acidic solution, stir and wash it, then filter it with deionized water until it is neutral, and then dry it and sieve it to obtain the Jerusalem artichoke residue-based hard carbon material for sodium ion battery electrode material.

[0034] Comparative Example 1 The Jerusalem artichoke residue without acid-base heat treatment was directly carbonized at 1400 ℃ and then acid-washed to remove impurities to obtain hard carbon material.

[0035] Performance Testing The Jerusalem artichoke residue-based hard carbon electrode materials prepared in Examples 1-3 and Comparative Example 1 were respectively used as negative electrode materials for sodium ion batteries. The hard carbon materials (Jerusalem artichoke residue-based hard carbon prepared in Example 1, Jerusalem artichoke residue-based hard carbon prepared in Example 2, Jerusalem artichoke residue-based hard carbon prepared in Example 3, Jerusalem artichoke residue-based hard carbon prepared in Comparative Example 1), carbon black and polyvinylidene fluoride were mixed in a mass ratio of 8:1:1, deionized water and N-methylpyrrolidone were added and ground in a mortar to prepare a uniform slurry, which was coated on a copper foil and dried in a vacuum drying oven at 60°C. The pole pieces were cut into discs with a diameter of 12 mm as negative electrodes for sodium ion batteries, and the sodium sheets were used as positive electrodes for sodium ion batteries. The electrolyte was a 1.0 M NaPF6 solution in diethylene glycol dimethyl ether, the solute was NaPF6, and the solvent was diethylene glycol dimethyl ether (DIGLYME). The battery was assembled in a glove box filled with argon, and the moisture content was less than 0.01 ppm and the oxygen content was less than 0.01 ppm, after assembly, the battery is subjected to a performance test of the charge and discharge specific capacity. Figure 4The rate performance test diagram of the sodium ion battery composed of the electrode materials prepared in Examples 1-3 and Comparative Example 1 at different current densities, the unit of current density is Ag. -1 ; Figure 5 The sodium ion battery composed of the electrode materials prepared in Examples 1-3 and Comparative Example 1 was -1 The statistical diagram of charge-discharge specific capacity under current density shows that the electrode materials prepared in Examples 1-3 have good electrochemical properties.

[0036] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0037] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. A method for preparing Jerusalem artichoke residue-based hard carbon electrode material, characterized in that: The preparation method comprises the following steps: (1) crushing Jerusalem artichoke residue and soaking it in an acidic solution for heat treatment, washing and drying to obtain a precursor material after removing part of the lignin, wherein the acidic solution is a sodium hypochlorite-acetic acid solution, a sulfuric acid aqueous solution or a hydrofluoric acid aqueous solution; the heat treatment temperature is 60-100° C. and the time is 2-12 h; (2) soaking the precursor material described in step (1) in an alkaline solution for alkaline boiling and heat treatment again, washing and drying to obtain a precursor material after removing part of the hemicellulose; the heat treatment time is 2-12 h, and the temperature is 60-100°C; (3) placing the precursor material after removing part of the hemicellulose in step (2) under a hot press for heating and compression, so that the cellulose in the material is densely packed to obtain a dense precursor material; (4) Placing the dense precursor material of step (3) in an inert atmosphere and subjecting it to high-temperature carbonization to obtain the electrode material; the temperature of the high-temperature carbonization is 800-1600° C., and the time is 0.1-6 h.

2. The preparation method according to claim 1, characterized in that: In step (1), the sodium hypochlorite-acetic acid solution is prepared by the following steps: 2-8 g of sodium hypochlorite and 4-16 mL of acetic acid are dissolved in 300-1000 mL of deionized water to obtain the sodium hypochlorite-acetic acid solution.

3. The preparation method according to claim 1, characterized in that: In step (1), the mass fraction of the aqueous sulfuric acid solution is 30-70 wt%.

4. The preparation method according to claim 1, characterized in that: In step (1), the mass fraction of the hydrofluoric acid aqueous solution is 5-30 wt%.

5. The preparation method according to claim 1, characterized in that: In step (2), the alkaline solution is a sodium hydroxide aqueous solution with a concentration of 2-10 wt% or a potassium hydroxide aqueous solution with a concentration of 2-10 wt%.

6. The preparation method according to claim 1, characterized in that: In step (4), the heating rate of the high temperature carbonization is 1-10°C / min.

7. The preparation method according to claim 1, characterized in that: In step (4), the inert gas is nitrogen or a hydrogen-argon mixture.

8. The preparation method according to claim 1, characterized in that: In step (4), after the high-temperature carbonization, the material needs to be naturally cooled to room temperature and ground to obtain the electrode material.

9. Jerusalem artichoke residue-based hard carbon electrode material prepared by the method according to any one of claims 1 to 8.

10. Use of the electrode material according to claim 9, characterized in that: The electrode material is used in the field of sodium ion batteries.

Citation Information

Patent Citations

  • Biomass hard carbon based on low crystalline cellulose content and preparation method and application thereof

    CN115064667A

  • Carbonaceous material and preparation method therefor, secondary battery comprising same, and electric device

    WO2024082307A1